Herbigation in a Vineyard through a Microjet Irrigation System - Fourie, J.C. (South African Journal of Enology and Viticulture, 2017)
The control of a variety of weeds by one post-emergence and five pre-emergence herbicides applied through a microjet irrigation system was determined. Oxadiazon and simazine gave good control of the weed species present in the trial. Napropamide controlled the different grass species effectively, but did not control the broadleafweeds. A combination of chlorsulfuron and metsulfuron methyl, in the ratio 3:1, controlled two grasses and one broadleaf weed effectively. Oryzalin controlled three of the predominent grass species effectively, but did not control the broadleaf weeds. It was found that herbigation with any of the five pre-emergence herbicides mentioned, can be utilized commercially to control susceptible weeds on medium textured soils in South African vineyards. A comparative study with simazine showed that herbigation through microjet irrigation systems can replace tractor boom sprayers as an application technique on medium textured soils. In the case of a microjet irrigation system with the emitters mounted at 3 m intervals, the micro jets should be situated on top of the irrigation line and the pressure in the system maintained at 200 kPa to ensure an efficient application. The post-emergence weed control by paraquat dichloride was unacceptable.